Comparison of Omega-3 Nutraceutical Dietary Supplement versus Topical Eye Drops for The Treatment of Dry Eye after Phacoemulsification - Jamil, Sana; Shafiq, Ummara; Boota, Wajeeha (Medical Journal of South Punjab, 2024)
Objective: To compare the effect of omega-3 dietary supplement vs topical conventional eye drops for the treatment of dry eye disease induced after un-complicated phacoemulsification. It was a Quasi-experimental study conducted from December 2023 to May 2024 in Al Ehsan eye trust hospital, Lahore. The study involved 42 patients who had developed dry eye after phacoemulsification. Patients were divided into groups. Treatment group was given omega-3 fish oil capsule and control group prescribed conventional topical eye drops for 3 months.Results: The mean pre-treatment values of all three tests improved significantly in both groups after 3 months. After 3 months of treatment the control group exhibited a mean OSDI score of 24.55(SD=1.92), compared to 19.20 (SD = 1.91) in the treatment group, though this difference was not statistically significant (t = -1.972, p = 0.923). This trend continued throughout for other two objective tests Schirmer test (t = 1.149, p = 0.289) and TBUT (t = 0.901, p = 1.032), where t-tests consistently yielded p-values above 0.05, suggesting no statistically significant divergence in tear production between groups.Conclusion: In conclusion, topical conventional eye drops and omega-3 dietary supplements (fish oil) both appear promising for the management of dry eye illness after unfussy phacoemulsification surgery.